Two contrasting Phanerozoic orogenic systems revealed by hafnium isotope data - Collins, William; Belousova, E.; Kemp, A.; Murphy, J. (Nature Publishing Group, Macmillan Publishers Ltd, 2011)
Two fundamentally different orogenic systems have existed on Earth throughout the Phanerozoic. Circum-Pacific accretionary orogens are the external orogenic system formed around the Pacific rim, where oceanic lithosphere semicontinuously subducts beneath continental lithosphere. In contrast, the internal orogenic system is found in Europe and Asia as the collage of collisional mountain belts, formed during the collision between continental crustal fragments. External orogenic systems form at the boundary of large underlying mantle convection cells, whereas internal orogens form within one supercell. Here we present a compilation of hafnium isotope data from zircon minerals collected from orogens worldwide. We find that the range of hafnium isotope signatures for the external orogenic system narrows and trends towards more radiogenic compositions since 550 Myr ago. By contrast, the range of signatures from the internal orogenic system broadens since 550 Myr ago. We suggest that for the external system, the lower crust and lithospheric mantle beneath the overriding continent is removed during subduction and replaced by newly formed crust, which generates the radiogenic hafnium signature when remelted. For the internal orogenic system, the lower crust and lithospheric mantle is instead eventually replaced by more continental lithosphere from a collided continental fragment. Our suggested model provides a simple basis for unravelling the global geodynamic evolution of the ancient Earth.